The Effect of Work Environment, Leadership and Motivation on Employee Turnover Intention in Alfamart Semarang - Sujito, Sujito (IJOSMAS, 2023)
- this study aims to empirically examine the effect of work environment, leadership and motivation on turn over intention with work spirit as an intervening variable at Alfamart Semarang area. The population of this study is all employees who are in the Alfamart area of Semarang, including Jatingaleh, Tembalang and Banyumanik, Semarang. With a total of 108 employees. In this study using a non-probability sampling technique, namely by using the Saturated Sampling (Census). Then the method of data collection through questionnaires and data analysis using SPSS 21 which includes validity, reliability, classical assumption test, multiple regression analysis, hypothesis testing using t test and R2 test. The results of this study indicate that all independent variables, namely Work Environment, Leadership and Motivation have a positive and significant effect on Turn Over Intention (Y). This is evidenced by the t-count value of 3.408 > t-table 1.659 with a significance level of 0.00 (.0.05). This shows that the work environment variable has a positive and significant effect on morale among Alfamart employees in Semarang. Motivation obtained t arithmetic value of 2.845 > t table 1.659 with a significance level of 0.00 (< 0.05). This shows that the motivation variable has a positive and significant effect on morale at Alfamart employees in Semarang. Leadership obtained t arithmetic value of 4.591 > t table 1.659 with a significance level of 0.00 (< 0.05). This shows that the leadership variable has a positive and significant effect on morale for Alfamart employees in Semarang. Morale (Y1) obtained t value of 15,771 > t table 1,659 with a significance level of 0.00 (< 0.05). This shows that the variable of work morale has a positive and significant effect on turnover attention of Alfamart employees in Semarang.